(untitled) - Wikoff, Karin (Santa Barbara, Calif., 2012)
This highly readable book provides the practical information needed to get started managing electronic resources throughout their lifecycle in an academic library
Keywords: Libraries,Thư viện; Electronic information resources,Special collections,Nguồn thông tin điện tử,Bộ sưu tập đặc biệt